Calculus II for dummies - Zegarelli, Mark (John Wiley & Sons, 2012)
"An easy-to-understand primer on advanced calculus topics Calculus II is a prerequisite for many popular college majors, including pre-med, engineering, and physics. Calculus II For Dummies offers expert instruction, advice, and tips to help second semester calculus students get a handle on the subject and ace their exams. It covers intermediate calculus topics in plain English, featuring in-depth coverage of integration, including substitution, integration techniques and when to use them, approximate integration, and improper integrals. This hands-on guide also covers sequences and series, with introductions to multivariable calculus, differential equations, and numerical analysis. Best of all, it includes practical exercises designed to simplify and enhance understanding of this complex subject." -- Vydavatelská anotace
Obsahuje rejstřík
Keywords: matematická analýza; integrály; integrální počet; řady (matematika); mathematical analysis; integrals; integral calculus; series; učebnice; textbooks